Economic justifcation for vegetable seed concept of sustainable organic production - Adžić, Slađan; Pavlović, Suzana; Zdravković, Jasmina (Economics of Agriculture, 2010)
According to the Offce for Statistics of the Republic of Serbia, vegetable production takes place on arround 284 000 ha. Only 490 hectares of this area is under organic production. This area is absolutely insuffcient in comparison with EU countries and neighboring countries. One of the reason for this low percentage of organic food in our country can be a lack of appropriate, certifed, organic seed. The task of seed companies is fnding out a solution that will allow suffcient market supply with organic seed and planting material, as soon as, possible. This paper was analyses the economics of beans, green beans, radish, small radish, lettuce and beetroot seed production, produced according principles of organic vegetable production. Based on indicators of analytical calculations, it was established that the biggest proft is made in the production of beetroot seed, and the lowest in bean and green bean seed cultivars. All analyzed seed production were economicall.